Empowering the Creative Economy Through the Development of MSME-Based Car Free Days in the Kolam Makale Area, Tana Toraja Regency - Abedneigo Carter Rambulangi; Althon Karaman Pongtuluran; Isak Pasulu; Elisabet Pali; Jemi Pabisangan Tahirs (Universitas Pahlawan Tuanku Tambusai, 2026)
Car Free Day (CFD) in the Kolam Makale area, Tana Toraja Regency, has developed into a public space that is not only used for community sports and recreational activities, but also as a center for creative economic activities through the involvement of Micro, Small, and Medium Enterprises (MSMEs). However, most MSMEs still face various obstacles, such as low business management capacity, lack of product innovation, limited digital marketing strategies, unattractive packaging designs, and the less than optimal use of Car Free Day as a promotional medium and to increase business competitiveness. This community service activity aims to increase the capacity of MSMEs through a creative economic empowerment program that includes training in business management, product innovation, branding, digital marketing, customer service, and assistance in developing business development strategies. The method used is Participatory Action Research (PAR) which involves MSMEs as active partners in every stage of the activity, starting from problem identification, program planning, training implementation, assistance, to evaluation of activity results. The results of the community service program demonstrate that this activity has been able to improve the knowledge and skills of MSMEs in managing their businesses more professionally, improve product and packaging quality, increase the use of digital media as a promotional tool, and strengthen marketing networks among business actors. Furthermore, Car Free Day increasingly functions as a productive public space that supports local economic growth and encourages the development of a creative economy based on regional potential. This program is expected to become a model for sustainable community empowerment in supporting the improvement of MSMEs' welfare and the development of creative economy destinations in Tana Toraja Regency